La regulación de los contratos internacionales en la Unión Europea - López-Tarruella Martínez, Aurelio (2015)
The aim of this paper is to provide a general overview of the rules of Private international law inthe European Union that deal with international contracts. The first part of the paper focuses on the analysis of the rules of Regulation 1215/2012 (Brussels I) that determine the international jurisdiction of the courts of the Member States to hear about contractual disputes. For this purpose a distinction is made between situations in which the parties have made use of forum-choice clauses and situations in which this has not been the case. The second part analyses Regulation 593/2008 (Rome I) on the law applicable to contractual obligations. As in the previous section, a distinction is made on whether the parties have agreed on the applicable law or not. This part also includes an analysis of the mechanisms in the Regulation allowing Member States to saveguardtheir national or EU interests.